2018
DOI: 10.1002/mc.22893
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin induces apoptosis and autophagy‐dependent cell death in cholangiocarcinoma through a DAPK1‐BECLIN1 pathway

Abstract: Cholangiocarcinoma (CCA) is a very aggressive cancer arising from the malignant transformation of cholangiocytes. Intrahepatic CCA is associated with reactive inflammation and intense fibrosis of the hepatobiliary tract. Dihydroartemisinin (DHA), the active compound found in Artemisia annua, has been shown to possess anti-tumor activity in a variety of human cancers, including hepatoma. Here, we tested the ability of DHA to specifically kill CCA cells and have investigated the underlying mechanisms. DHA induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…Importantly, its cytotoxic effects were cancer-cell-specific, since only slight toxicity was observed on immortalized cholangiocytes. Beclin1 activation is crucial for dihydroartemisinin action since its genetic depletion or its pharmacologically-mediated degradation inhibits autophagy activation and partially protects CCA cells from dihydroartemisinin treatment [154]. Another drug that promotes Beclin1 activation is pristimerin, which inhibited CCA cell growth in vitro and in vivo, decreasing apoptosis-related proteins Bcl-2, Bcl-XL and procaspase-3, similar to the effect of BH3 mimetics, suggesting pristimerin promotes Beclin1 activation and initiation of autophagy.…”
Section: Autophagy Activatorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, its cytotoxic effects were cancer-cell-specific, since only slight toxicity was observed on immortalized cholangiocytes. Beclin1 activation is crucial for dihydroartemisinin action since its genetic depletion or its pharmacologically-mediated degradation inhibits autophagy activation and partially protects CCA cells from dihydroartemisinin treatment [154]. Another drug that promotes Beclin1 activation is pristimerin, which inhibited CCA cell growth in vitro and in vivo, decreasing apoptosis-related proteins Bcl-2, Bcl-XL and procaspase-3, similar to the effect of BH3 mimetics, suggesting pristimerin promotes Beclin1 activation and initiation of autophagy.…”
Section: Autophagy Activatorsmentioning
confidence: 98%
“…Four natural compounds have been recently described to induce CCA cell death, implicating the activation of autophagy as a mediator of their cytotoxic effects:piperlongumine (small molecule extracted from Piper longum plant [151]), pterostilbene (an active constituent of blueberries [152]), pristimerin (a triperpenoid isolated from Maytenus heterophylla [153]) and dihydroartemisinin (an active compound found in Artemisia annua [154]). Although it has been proven that autophagy induction is necessary for their mechanism of action, the specific molecular mechanisms governing their autophagy modulation abilities are not fully understood yet.…”
Section: Autophagy Activatorsmentioning
confidence: 99%
“…Besides, EGCG-DHA (docosahexaenoic) ester, a lipophilic derivative of EGCG, shows improved anti-oxidative effects compared to EGCG, and suppresses colon carcinogenesis in mice [112,113]. In the last decade, many studies were carried out using EGCG-loaded nanoparticles including FA-NPS-PEG and FA-PEG-NPS (epigallocatechin gallate-β-lactoglobulin nanoparticles), EGCG-SLN (solid lipid nanoparticle), DT-EGCG-nanoethosomes, FCS-EGCG-NPs (chitosan coated nanoparticles), EGCG-dispersed selenium nanoparticles, 198 AuNP-EGCg (gold nanoparticles), EGCG-loaded microspheres (EGCG/MS), and FCMPs (ferritin-chitosan Maillard reaction products) [6,110,[114][115][116][117][118][119][120][121]. These EGCG nanoparticles can improve the targeting ability and efficacy of EGCG, which greatly promote the clinical application and development of EGCG analogs.…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…Similarly, ART induces apoptosis in murine mastocytome P815 cells and hamster kidney adenocarcinoma BSR cells, and inhibits tumor growth in P815 xenograft mice [177]. Moreover, autophagy plays a vital role in ART-mediated anti-cancer activities [190,[197][198][199][200][201]. DHA can induce autophagy-dependent cell death in human cervical cancer HeLa cells, cholangiocarcinoma KKU-452, KKU-023 and KKU-100, and tongue squamous cell carcinoma Cal-27 cells [190,198,199], while ART induces autophagy-mediated cell cycle arrest in human ovarian cancer SKOV3 cells [200].…”
Section: Artemisininsmentioning
confidence: 99%
“…Studies indicated that DHA induced autophagy in different types of cancer cells [22,23,28], whether DHA could mediate autophagy in esophageal cancer remains to be clarified. We transfected GFP-LC3 plasmids into Eca109 cells with the help of lipofectamine 2000 reagent, and massive green LC3 puncta could be observed post 48 h in cells treated with DHA compared with DMSO (Fig.…”
Section: Dha Induces Autophagy In Eca109 Cellsmentioning
confidence: 99%